Analysis of Accounting Information Systems in Supporting Internal Control of People's Business Credit (KUR): Analisis Sistem Informasi Akuntansi dalam Mendukung Pengendalian Intern Terhadap Pemberian Kredit Usaha Rakyat (KUR) - Putra, Icksa Abdi; Maryanti, Eny (Universitas Muhammadiyah Sidoarjo, 2022)
A proper business is a business carried out by prospective debtors that can be profitable so that prospective debtors are able to pay interest and can repay all debts/credit principal obligations within the time agreed upon between the executing bank and the debtor. While what is meant by not yet bankable is MSME-K that has not met the financing requirements of the implementing bank in providing collateral or it can be said that it has not been able to meet the financing requirements in accordance with the provisions of the implementing bank. This research uses qualitative methods, according to Sugiyono (2011) qualitative research methods is a research method based on post-positivism philosophy, used to examine the condition of natural objects, (as opposed to experimentation) where the researcher is the key instrument, the sampling of data sources is carried out purposively and snowball, the collection technique is tri-angulation (combined). , data analysis is inductive or qualitative, and qualitative research results emphasize meaning rather than generalization. Based on the above analysis in terms of the credit assessment used in granting credit decisions. So it can be concluded as follows: Implementation of the Accounting Information System and internal control in the provision of People's Business Loans to the Limited Liability Company of Bank BRI Jabon unit which includes the Control Environment Component, Risk Assessment Component, Control Activity Component, Information and Communication Component, Monitoring / Supervision Component. according to COSO